Oxalate Pushes Efficiency of CsPb0.7Sn0.3IBr2 Based All‐Inorganic Perovskite Solar Cells to over 14%. Issue 11 (12th February 2022) - Zhang, Weihai; Liu, Heng; Qi, Xingnan; Yu, Yinye; Zhou, Yecheng; Xia, Yu; Cui, Jieshun; Shi, Yueqing; Chen, Rui; Wang, Hsing‐Lin
Abstract: All‐inorganic CsPbIBr2 perovskite solar cells (PSCs) have recently gained growing attention as a promising template to solve the thermal instability of organic–inorganic PSCs. However, the relatively low device efficiency hinders its further development. Herein, highly efficient and stable CsPb0.7 Sn0.3 IBr2 compositional perovskite‐based inorganic PSCs are fabricated by introducing appropriate amount of multifunctional zinc oxalate (ZnOX). In addition to offset Pb and Sn vacancies through Zn 2+ ions incorporation, the oxalate group can strongly interact with undercoordinated metal ions to regulate film crystallization, delivering perovskite film with low defect density, high crystallinity, and superior electronic properties. Correspondingly, the resulting device delivers a champion efficiency of 14.1%, which presents the highest reported efficiency for bromine‐rich inorganic PSCs thus far. More importantly, chemically reducing oxalate group can effectively suppress the notorious oxidation of Sn 2+, leading to significant enhancement on air stability. Abstract : Highly efficient CsPb0.7 Sn0.3 IBr2 perovskite solar cells (PSCs) are achieved via introducing zinc oxalate (ZnOX) as additive. ZnOX not only reduces the metal ions related trap states but also modulates film crystallization, resulting in a record device efficiency of 14.1%. In particular, chemically reducing oxalate can effectively suppress the oxidation of Sn 2+, contributing to devices with much improved long‐term air stability.